Government Policies and Traditional Institutions’ Reforms for Efficient Local Governance in Ogun State, Nigeria - Moliki , Ahmed Olawale; Peju-Rosenje, Temitope O. (Kashere Journal of Politics and International Relations, 2023)
Globally, government policies are made for the purpose of providing services, executing projects and programmes that will make life more meaningful for the citizenry. While reforms are made on traditional institutions to keep them in pace with the emerging trends in development and civilisation and more relevant to local governance since the society is conceived as dynamic and evolving. More often than not, the Ogun State situation in Nigeria has been at variance with this norm. This paper investigated how government policies and traditional institutions’ reforms could enhance efficiency in local governance in Ogun State, Nigeria. It used exploratory method and gathered data through secondary source of data. It adopted democratic participatory theory and the efficiency services theory models as it theoretical bases. It observed that government has been making policies to improve the welfare of citizens since colonial era, while traditional institutions’ reforms have been made at the grassroots since the commencement of colonial administration. It concluded that this has created a gap between the government and the people, especially with those in the remotest and rural areas of the State, where government presence is non-evident. It recommended that traditional institutions should be given the opportunity to creditably render useful services to the local people in order to make life more abundant for the poor majority. Also, specific functions should be arrogated to traditional institutions through reforms.